Diseño de un plan de publicidad para la feria de comercialización de ganado bovino en asociación 24 de mayo parroquia Sevilla Don Bosco. - Delgado Rivadeneira, Fausto Xavier (2024)
The cattle fair in 24 de mayo Association, Sevilla Don Bosco parish, stands out for its approach on livestock tradition, quality events and promotion of sustainable practices. Its promotion strategies, backed by a favourable survey, are focused on advertising in specialized media and effective presence in social networks. Brand identify has been strengthened but faces challenges in balancing tradition with innovation. The positive impact on the local community, both in terms of the economy and knowledge sharing, is evident. Recommendations point to strengthening the digital presence, updating the website to improve the user experience, and incorporating technology to enrich the participation of visitors and speakers. The importance of consolidating strategic alliances and periodically evaluating to adapt to market trends is highlighted. Promoting sustainable practices and offering training programs are key aspects for the constant growth of the fair.